(untitled) (Papeles, 2025)
The article presents progress of the research project “Democratic openness and its impact on Social Work. Fields of professional intervention, new public institutions and the relationship with the social policies of the provincial state (1983-1987)” that we developed in the Faculty of Social Sciences of the National University of Córdoba with endorsement and financing from the Secretariat of Science and Technology of the National University of Córdoba (Secyt UNC). We will address the fields of intervention of Social Work as derived or constituted from the development of particular social policies, which address various expressions of the social issue, in which our profession was in demand and developed a practice with a technical profile, of a strongly interventional nature. In the written productions of the period reviewed, the fields of application or action of the Social Service are defined based on a segmentation of reality, of the social, which is presented as multiple particular problems that will be addressed in a fragmented manner by different " state and non-state institutional sectors. The fields of action, the fields of application of Social Work are then defined based on this segmentation of reality and the fragmentation in the responses to these particular social problems.